Molecular characterization of Newcastle disease virus (AOAV-1) obtained from Western region of Libya - Abdulwahab Kammon; Elhadi Rammah; Abdulhamid Giweli; Isabella Monne (Open Veterinary Journal)
Background: Since its discovery in 1926, Newcastle Disease is still emerging in many avian species worldwide causing severe economic losses due to high mortality. Aim: This article aims to discuss the challenge of virulent Newcastle Disease (ND) in poultry in Libya, focusing on recent outbreaks investigated in Alzintan, Alrayaina, Nalut, and Surman, cities located in the western region of Libya. Methods: Clinical signs and lesions were recorded, and tissues, as well as tracheal and cloacal swabs, were collected. RNA extraction was performed for confirmation using PCR and sequencing. Results: Mortality in general reached 50-100% in vaccinated flocks with respiratory distress, diarrhea, swelling of the face and nasal discharges. Necropsy revealed severe hemorrhages in the proventriculus, necrosis and hemorrhages in the intestine and cecal tonsils. All tested samples were positive for AOAV-1 using rRT-PCR and genetic analysis. The sequences obtained are referable to AOAV-1, which is the same strain in all tested samples. The amino acid sequences deduced from the cleavage site of the F protein are referable to a velogenic strain of AOAV-1 belongs to genotype VII.2. The detected strains in the current study revealed 86-91 % identity with European isolates identified between 2020-2022 and isolates from Asia and Africa and 97% identity to the previous isolated Libyan strains in 2013 and 2016. It is slightly different by the presence of amino acid lycine at the position 111 on the cleavage site of the F0 gene as compared to previous Libyan strains in which arginine was found in the same position. The nucleotides sequence at this position changed from (aga) in AOAV-1 strains of years 2013 and 2016 to (aag) of the year 2023. Conclusion: Newcastle disease remains a significant threat to the poultry industry in Libya. Therefore, there is an urgent need to conduct an epidemiological study with a representative number of samples from all regions of the country, alongside the implementation of an inactivated vaccine targeting genotype VII. [Open Vet J 2024; 14(9.000): 2453-2462]